2021
DOI: 10.34293/management.v8i3.3587
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Customer Relationship Management Strategies in Creating Customer Loyalty and Satisfaction: An Analytical Study

Abstract: Customer Relationship Management (CRM) is significantly regarded in the market for existing, likewise, current customers. This paper inspected the effect of client relationship management (CRM) components on consumer loyalty and satisfaction. A fair CRM (customer relationship the board) program that helps the association satisfy the customer, the investigation study would examine uncommon systems and methods for setting up effective CRM to satisfy the customers. The inspiration for driving the examination was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Evidence also indicated that customer relationship management practices have consequences for product/service innovation capability [41][42][43], customer loyalty, and customer satisfaction [44] service quality which enable firms to gain competitive advantage [3].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence also indicated that customer relationship management practices have consequences for product/service innovation capability [41][42][43], customer loyalty, and customer satisfaction [44] service quality which enable firms to gain competitive advantage [3].…”
Section: Literature Reviewmentioning
confidence: 99%